The importance of psychological constructs for training volume and performance improvement: A structural equation model for youth speed skaters - Elferink Gemser, M. T.; De Roos, I.; Torenbeek, M.; Fokkema, T.; Jonker, L.; Visscher, C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: In the process of training and reaching an expert performance level in sport, psychological characteristics play a crucial facilitating role (Starkes & Ericsson, 2003). The relation between self-regulated learning, intrinsic motivation, and goal orientation with training volume and performance improvement is still unknown. Methods: 63 talented Dutch speed skaters (n=35 male; n=28 female) aged 11 to 22 filled in the Self-Regulation of Learning-Self-Report Scale (SRL-SRS; Toering et al., 2012), Sports Motivation Scale (SMS; Pelletier et al., 1995), Task and Ego Orientation in Sports Questionnaire (TEOSQ; Duda & Nicholls, 1992) and a questionnaire for training volume. Performance im-provement over one competitive season was based on the national ranking of the Dutch National Speed Skating Association. Results: Structural Equation Modeling in LISREL showed that the model fitted the data (÷2(11)=15.49, p=.16, SRMR=.089, CFI=.97, NNFI=.94, RMSEA=.077). Task orientation and intrinsic motivation were positively associated with each other (.59) and with the selfregulation learning skills planning and reflection (.25-.31). Reflection was positively related to training volume (.24) and a higher performance improvement (.22). Additionally, ego orientation was positively related to performance improvement (.31). Also a direct positive relation between training volume and performance improvement was found (.59). All relations were significant (p<.05). Discussion: The present findings support the integrated view on psychological constructs in talent development, and underline the importance of psychology in talent development in sport. The clear relations between several psychological constructs and their combined importance for training volume and performance improvement over one season are relevant for those working with talented athletes. It would be valuable to monitor and develop psychological factors in talent development programs, particularly goal orientations, intrinsic motivation, planning and reflection. These factors seem to play an important role in the development of performance and in reaching a high performance level.